Innovative Strategies for Inclusive and Equitable ASN Talent Management: Insights and Breakthroughs from Indonesia's Public Sector Webinar Series - Puspasari, Azizah; Hapsari, Leonita (Iapa Proceedings Conference, 2024)
The effective implementation of talent management for civil servants (ASN) is critical to achieving a professional and efficient bureaucracy in the Indonesian government. In 2023, the Center for ASN Management Studies at the National Civil Service Agency (LAN) organized a series of twelve webinars titled "Sharing Best Practices in Implementing ASN Talent Management: Accelerating the Realization of Future Leaders," focusing on advocating for the implementation of ASN talent management within Ministries, Agencies, and Local Governments in Indonesia. This study employs qualitative content analysis to examine the key themes and insights garnered from these webinars. The research explores the significance of talent management in enhancing social inclusion, gender representation, and social equity in the public sector. The primary objective is to identify the driving factors behind successful talent management practices and the outcomes they generate. Utilizing a thematic analysis approach, the study analyzes webinar content to highlight best practices, challenges, and innovative strategies in ASN talent management. Findings indicate that a robust talent management framework significantly contributes to organizational goals, creating an inclusive work environment, and promoting gender equality. The study concludes that insights from these webinars provide valuable recommendations for policymakers and public administration leaders. These findings have broad implications for enhancing talent management policies and practices, ultimately improving the sustainability of public administration in Indonesia.